2012
DOI: 10.1002/hep.24698
|View full text |Cite
|
Sign up to set email alerts
|

miR-25 Targets TNF-Related Apoptosis Inducing Ligand (TRAIL) Death Receptor-4 and Promotes Apoptosis Resistance in Cholangiocarcinoma

Abstract: It has been established that microRNA expression and function contribute to phenotypic features of malignant cells, including resistance to apoptosis. While targets and functional roles for a number of microRNAs have been described in cholangiocarcinoma, many additional microRNAs dysregulated in this tumor have not been assigned functional roles. In this study, we identify elevated miR-25 expression in malignant cholangiocarcinoma cell lines as well as patient samples. In cultured cells, treatment with the Smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 38 publications
5
121
0
1
Order By: Relevance
“…Thus, miR-25 may be a potential therapeutic target in the treatment of vascular disease. Previous studies have demonstrated that miR-25 is able to regulate various developmental and cellular processes, and is implicated in a number of human diseases (31)(32)(33). miR-25 is known to be important in several types of cancer, including hepatocellular carcinoma, and colon, gastric and lung cancer (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miR-25 may be a potential therapeutic target in the treatment of vascular disease. Previous studies have demonstrated that miR-25 is able to regulate various developmental and cellular processes, and is implicated in a number of human diseases (31)(32)(33). miR-25 is known to be important in several types of cancer, including hepatocellular carcinoma, and colon, gastric and lung cancer (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…miR-25 belongs to the miR106b-25 cluster that was involved in development and tumorigenesis with the miR-17-92a cluster (57,58). miR-25 itself has been demonstrated to regulate apoptosis by targeting Bim in human ovarian cancer (59) and promote apoptosis resistance in cholangiocarcinoma by targeting NF-related apoptosis-inducing ligand (TRAIL) death receptor-4 (40). In addition, miR-25 with other miRNAs collectively influences MKK4 abundance during replicative senescence (60), but its function in innate immunity is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, ~20% of patients are not sensitive to this immunochemotherapy, and these patients then relapse following the first-line regimen and tend to respond poorly to additional chemotherapy lines. Studies suggest that abnormalities in signaling pathways including NF-YB, SFPQ, MYBL2, BIM/APAF-1, AEG-1, BCL-2, XIAP, DR4 and ABCA1 are involved in primary or acquired chemoresistance and poor prognosis (3)(4)(5)(6)(7)(8)(9). Therefore, the identification of chemoresistance-related biomarkers may achieve a better prediction of chemotherapy efficacy for DLBCL patients, and could be used for the diagnosis of poor outcome cases, providing an advanced treatment strategy.…”
Section: Introductionmentioning
confidence: 99%